Enterococci from piglets - probiotic properties and responsiveness to natural antibacterial substances - Strompfová, Viola; Lauková, Andrea (Folia microbiologica, 2009)
Fifty-five strains of enterococci isolated from the piglet intestine were characterized in vitro for probiotic activity. Identification of the isolates revealed Enterococcus faecium as the predominant species (84 %). Forty strains (73 %) were found to produce bacteriocin-like substances (only into solid media) with activity almost only toward Gram-positive genera. Thirty-eight % of strains were resistant to tetracycline, 27 % to chloramphenicol, 18 % to erythromycin and 16 % to vancomycin. In addition to control of strain safety, 6 % of isolates were beta-hemolytic and 16 % produced gelatinase. Seven strains selected for further probiotic assays exhibited sufficient survival rate at pH 3.0 after 3 h, in the presence of 1 % ox-bile and lysozyme after 1 d (over 107 CFU/mL in all tests). The adhesion of tested strains to porcine and human intestinal mucus was found in a similar range (1.4-14.0 % and 1.4-17.6 %, respectively). In accordance with current research effort to use and/or to combine various health promoting substances, the sensitivity of all isolates toward plant extracts and toward bacteriocins produced by animal and environmental strains was determined. All enterococci were sensitive toward oregano and sage extracts and toward one (E. faecium EF55--chicken isolate, activity of 25 600 AU/mL) of ten bacteriocin substances. It means that a similar anti-enterococcal potential of some bacteriocin substances may be observed as for certain plant extracts.
Keywords: financování organizované; Animals; Probiotics; Enterococcus; Origanum; Bacteriocins; mikrobiální testy citlivosti; mikrobiální viabilita; Bile Acids and Salts; rostlinné extrakty; antibióza; gastrointestinální trakt; Anti-Bacterial Agents; prasata; Muramidase; žlučové kyseliny a soli; Mucins; bakteriální léková rezistence; dobromysl (rod); Financing, Organized; Microbial Sensitivity Tests; kyseliny; muciny; Microbial Viability; probiotika; bakteriociny; Swine; muramidasa; Plant Extracts; zvířata; Gastrointestinal Tract; antibakteriální látky; Drug Resistance, Bacterial; bakteriální adheze; Antibiosis; Acids; Bacterial Adhesion